Minichromosome maintenance protein 2 (MCM2) is a stronger discriminator of increased proliferation in mucosa adjacent to colorectal cancer than Ki-67. Issue 4 (12th May 2008) - Hanna-Morris, A; Badvie, S; Cohen, P; McCullough, T; Andreyev, H J N; Allen-Mersh, T G
Abstract : Background: Loss of control of mucosal crypt cell proliferation resulting in a hyperproliferative field change occurs early in the adenoma-carcinoma sequence. Ki-67, the current gold-standard marker of cellular proliferation, is a cell cycle protein that may lack sensitivity in demonstrating altered mucosal crypt cell dynamics. Minichromosome maintenance protein 2 (MCM2) has a specific role in DNA replication and has been proposed as a new marker for screening for colorectal cancer. Aim: To compare the expression of Ki-67 with that of MCM2 in colorectal mucosa associated with colorectal cancer. Methods: Ki-67 and MCM2 immunostaining was performed on serial sections taken from formalin-fixed, paraffin-embedded specimens. Labelling indices were calculated by counting the proportion of positively stained nuclei in representative areas of adenocarcinoma, and in equivalent superficial, middle and basal crypt compartments of mucosa sampled 1 cm from tumour (Ca1) and 10 cm from tumour (Ca10). Results: Specimens were obtained from 43 patients (27 adenocarcinoma, 16 no-cancer controls). Most nuclei in specimens of adenocarcinoma stained positively for MCM2 and Ki-67. In Ca1 and Ca10 samples, significantly greater staining of MCM2 than Ki-67 was seen in all crypt compartments. Receiver operator characteristic curve analysis suggested that proliferation changes (assessed by either MCM2 or Ki-67 staining) in Ca10, but not in Ca1, mucosa significantly predicted origin from a carcinoma-associated colon. Conclusions: MCM2 was more sensitive than Ki-67 in identifying colorectal mucosal proliferation. Increased proliferation (assessed by either MCM2 or Ki-67 staining) in mucosa at 10 cm, but not at 1 cm, from carcinoma significantly predicted origin from a carcinoma-associated colon.